(3QSGdI aj HYV eTcdGJ hEjQGOGJs - (3bQej RGOIs
(3ChdgG (B:s
(3MeOkG def HeYhfJg JcTa GdeYVdGJ hHYO ajbhd eMeO Hf YHO Gddg deG JbjOJ ef EHJOGA GdJcdja s
(3BNQgG (B:s
(3fUag cdMjI hfUag ddejJg ajQLY fUa GdejJg ddCe hgcPG jOhQ gPG GdSge CHOkG hdG jfbWY aeG GdMjdI ai EfbWGYg hGdMeO ddg hMOg hUdi Gddg Ydi ef dGfHi HYOg eMeO hBdg hUMHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdC;eOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs